The university library performance analysis: current state and prospects - P. A. Boldyrev (Библиосфера, 2014)
The objective of library activities modernization, determined by dynamic processes peculiar for political, economic and social life of our society, faces at a modern stage of higher school and academic library development. To solve the problem we need a strategy for achieving sustainable parity between the external environment and internal capabilities of the library. A shift from the funding by the library presence to financing focused on the final product make the library use available resources more effective. The analysis of statistical parameters of the academic library precedes elaboration of the strategic directions of the library activity. Modern library statistics is based on accounting. On its basis it was performed statistical records, which are quantitative indices of the library performance, reflecting main amount of work carried by the library. The article analyzes main statistical indicators of the library activity, such as: the number of users, books circulation, visits. The current state of Orenburg State University Scientific Library (OSU SL) is characterized. The comparison of absolute and average indicators of the library activity was carried out for several years, trends were identified, and the prognosis of its development was determined for the mid- and long-term periods. Based on the statistical analysis of OSU SL activity for 2009-2013 it was clearly shown the influence of e-books of the electronic library systems on attendance and traditional circulation. The process of traditional collection displacement takes place, which scales depend on the readers demand for e-books and the level of e-library systems development. On the background of the library parameters falling to identify new growth points and strategic orientations is of great significance. It’s required a set of actions for creation and implementation of particular types of strategies as components of the general library strategy. As a result, a consistent, unified and integrated model of decisions should be formed, that affects the development of the library infrastructure, features of information resources generation, modification of provided information services, as well as the staff skills and functional.